Polyether polymer, polyether electrolyte for lithium ion secondary battery, composite solid electrolyte for lithium ion secondary battery, and lithium ion secondary battery

CN122953256APending Publication Date: 2026-10-20OSAKA SODA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580021078.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-27
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

[0039]本发明的聚醚聚合物是具有特定结构单元的聚合物,因此能够抑制与硫化物系固体电解质的副反应,并且具有高离子迁移数。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention provides a polyether polymer capable of suppressing side reactions with sulfide-based solid electrolytes and possessing a high ion mobility number; a polyether electrolyte for lithium-ion secondary batteries using this polyether polymer; a composite solid electrolyte for lithium-ion secondary batteries; and a lithium-ion secondary battery. The invention relates to a polyether polymer containing 20 mol% or more of an X unit within 100 mol% of the structural unit, wherein the X unit is a specific structural unit derived from oxetane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to polyether polymers, polyether electrolytes for lithium-ion secondary batteries, composite solid electrolytes for lithium-ion secondary batteries, and lithium-ion secondary batteries. Background Technology

[0002] All-solid-state batteries are batteries with a solid electrolyte layer between the positive and negative electrode layers. Compared with liquid batteries with electrolytes containing flammable organic solvents, they have advantages such as easier simplification of safety devices.

[0003] All-solid-state lithium-ion batteries have high energy density due to the use of battery reactions that accompany the movement of lithium ions. In addition, they have attracted much attention for using solid electrolytes instead of electrolytes containing organic solvents as the electrolyte between the positive and negative electrodes (e.g., Patent Document 1).

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2020-107414 Summary of the Invention

[0007] The problem the invention aims to solve

[0008] Sulfide-based solid electrolytes are sometimes used as inorganic solid electrolytes in all-solid-state batteries. However, sulfide-based solid electrolytes generally undergo side reactions upon contact with other materials constituting the battery, and the sulfide-based solid electrolyte itself may decompose. Therefore, materials that can suppress side reactions with sulfide-based solid electrolytes and inhibit their decomposition reactions are desirable.

[0009] Furthermore, since inorganic solid electrolytes have few contact points, there are existing methods for adding polymeric electrolytes to them to improve ionic conductivity. In the prior art, polyether-based polymers with polyethylene oxide (PEO) as the main component are used as the polymeric electrolyte added to the inorganic solid electrolyte. However, the inventors' research results show that there is still room for improvement in the ability of conventional polyether-based polymers to suppress side reactions with sulfide-based solid electrolytes while maintaining high ion transport numbers. It should be noted that in this technical field, inventions generally aiming to improve ionic conductivity are common; focusing on ion transport numbers, which are contradictory to ionic conductivity, is a relatively new approach.

[0010] The object of the present invention is to provide a polyether polymer capable of suppressing side reactions with sulfide-based solid electrolytes and having a high ion mobility number, a polyether electrolyte for lithium-ion secondary batteries using the polyether polymer, a composite solid electrolyte for lithium-ion secondary batteries, and a lithium-ion secondary battery.

[0011] Solution for solving the problem

[0012] To achieve the above objectives, the inventors conducted various studies and discovered that specific polyether polymers can suppress side reactions with sulfide-based solid electrolytes and have high ion transference numbers, thus completing this invention.

[0013] The present invention is described below.

[0014] Item 1

[0015] A polyether polymer comprising more than 20 mol% of X units in 100 mol% of structural units, wherein the X units are structural units derived from oxetane as shown in the following general formula (1).

[0016]

[0017] [In the formula, R] 1 Whether the same or different, it is an alkyl group with 1 to 6 carbon atoms, R 2 Whether they are the same or different, it is -CH2O(CH2). a O(CH2) b The alkylene glycol alkyl ether group represented by H has the same or different repeating unit number a, which is an integer from 1 to 10, and the same or different repeating unit number b, which is an integer from 0 to 6.

[0018] Item 2

[0019] The polyether polymer according to item 1 further comprises Z units, said Z units being structural units derived from oxetane as shown in the following general formula (2).

[0020] In 100 mol% of the structural unit, the content of X unit is 20~99.9 mol% and the content of Z unit is 0.1~20 mol%.

[0021]

[0022] [In the formula, R] 1 Whether the same or different, it is an alkyl group with 1 to 6 carbon atoms, R 4 Same or different, for -CH2OR 8 The crosslinking group shown contains an olefinic unsaturated double bond, R 8 The same or different, being acryloyl, methacryl, allyl, or methylallyl.

[0023] Item 3

[0024] The polyether polymer according to item 1 or 2 further comprises a Y unit, said Y unit being a structural unit derived from oxetane as shown in the following general formula (3).

[0025] In 100 mol% of the structural unit, the content of X unit is 20~98.9 mol%, the content of Y unit is 1~79 mol%, and the content of Z unit is 0.1~20 mol%.

[0026]

[0027] [In the formula, R] 1 Whether the same or different, it is an alkyl group with 1 to 6 carbon atoms, R 3 Whether they are the same or different, they are hydrogen atoms or -CH2O(CH2). c (CHR 6 ) d (CH2) e R 7 The group shown, R 6 Whether the same or different, it is an alkyl group with 1 to 4 carbon atoms, R 7 The repeating units (c) may be the same or different, and are either hydrogen atoms, hydroxyl groups, nitrile groups, trifluoromethyl groups, alkoxy groups, or optionally cyclic ether groups with substituents. The number of repeating units (c) may be the same or different, and is an integer from 0 to 4. The number of repeating units (d) may be the same or different, and is an integer from 0 to 4. The number of repeating units (e) may be the same or different, and is an integer from 0 to 10.

[0028] Item 4

[0029] A polyether electrolyte for lithium-ion secondary batteries comprises the polyether polymer described in any one of claims 1 to 3 and a lithium salt compound.

[0030] Item 5

[0031] A composite solid electrolyte for lithium-ion secondary batteries, comprising an inorganic solid electrolyte and the polyether electrolyte for lithium-ion secondary batteries described in item 4.

[0032] Item 6

[0033] According to item 5, the composite solid electrolyte for lithium-ion secondary batteries is a sulfide-based solid electrolyte.

[0034] Item 7

[0035] A lithium-ion secondary battery that uses the polyether electrolyte for lithium-ion secondary batteries described in item 4.

[0036] Item 8

[0037] A lithium-ion secondary battery that uses the composite solid electrolyte for lithium-ion secondary batteries described in item 5.

[0038] The effects of the invention

[0039] The polyether polymer of the present invention is a polymer with specific structural units, thus enabling it to suppress side reactions with sulfide-based solid electrolytes and possessing a high ion transference number. Detailed Implementation

[0040] The polyether polymer of the present invention contains more than 20 mol% of X units per 100 mol% of structural units, wherein the X units are structural units derived from oxobutane as shown in the aforementioned general formula (1). This enables the suppression of side reactions with sulfide-based solid electrolytes and results in a high ion transference number (lithium ion transference number).

[0041] The reason for achieving the above-mentioned effects in this invention is not yet clear, but it is speculated as follows.

[0042] It is believed that lithium ions are coordinated with and transported to the highly mobile side chains, namely alkylene glycol alkyl ether groups, thus exhibiting a high lithium ion transference number. In R 1 When the alkyl group has 1 to 6 carbon atoms, the steric hindrance effect introduced into the polyether structure hinders the coordination of lithium ions with the ether oxygen in the main chain, and there is a tendency to obtain this effect more appropriately. Although nonpolar groups such as alkyl groups do not directly coordinate with lithium ions, they are considered to participate in the optimization of the coordination state between polar groups such as ether oxygen and lithium ions. In addition, regarding sulfide resistance, it is also believed that by appropriately maintaining the distance between the ether oxygen in the main chain and the side chain, the coordination with lithium ions is moderated, thus suppressing the reaction with sulfide-based solid electrolytes. Similarly, regarding sulfide resistance, in R... 1 In the case of alkyl groups with 1 to 6 carbon atoms, the steric hindrance effect brought about by introducing alkyl groups tends to be more suitable for obtaining the desired effect.

[0043] <Polyether polymers>

[0044] The polyether polymer of the present invention contains 20 mol% or more of X units per 100 mol% of structural units, wherein the X units are structural units derived from oxetane as shown in the following general formula (1). In the polyether polymer of the present invention, each X unit may be the same or different. Therefore, the polyether polymer of the present invention may be a polymer composed of one or more units belonging to the X unit. In the polyether polymer of the present invention, each unit in the X unit is preferably the same.

[0045]

[0046] [In the formula, R] 1Whether the same or different, it is an alkyl group with 1 to 6 carbon atoms, R 2 Whether they are the same or different, it is -CH2O(CH2). a O(CH2) b The alkylene glycol alkyl ether group represented by H has the same or different repeating unit number a, which is an integer from 1 to 10, and the same or different repeating unit number b, which is an integer from 0 to 6.

[0047] R as in equation (1) 1 The alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms, more preferably 1 to 2 carbon atoms) can be linear or branched, and examples include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl, and hexyl. Among these, methyl and ethyl are preferred.

[0048] R as in equation (1) 1 Based on the reasons that it can easily become a steric hindrance, can appropriately suppress the coordination of lithium ions to ether oxygen in the main chain, obtain a higher ion transference number, and can suppress side reactions with sulfide-based solid electrolytes, alkyl groups with 1 to 6 carbon atoms are preferred.

[0049] R in equation (1) 2 -CH2O(CH2) a O(CH2) b The alkylene glycol alkyl ether group represented by H exhibits superior molecular mobility compared to the polymer backbone and has a structure that appropriately maintains the distance between oxygen atoms, thus resulting in a high ion transference number.

[0050] R in equation (1) 2 In equation (1), a is an integer from 1 to 10, preferably an integer from 1 to 9, more preferably an integer from 2 to 9, even more preferably an integer from 2 to 8, particularly preferably an integer from 2 to 7, most preferably an integer from 2 to 6, even more preferably an integer from 3 to 6, and even more preferably an integer from 4 to 6. R in equation (1) 2 In this context, b is an integer from 0 to 6, preferably an integer from 0 to 4, more preferably an integer from 1 to 3, and even more preferably an integer from 1 to 2.

[0051] The following shows a preferred embodiment of the structural unit X derived from oxetane, represented by formula (1). Preferably, the structural unit is represented by formulas (1-1) to (1-3), more preferably by formulas (1-1) and (1-2), and even more preferably by the structural unit represented by formula (1-1).

[0052]

[0053] Preferably, the polyether polymer of the present invention, in addition to the aforementioned X units, also includes Z units, which are structural units derived from oxetane and represented by the following general formula (2). This can improve the mechanical properties of the crosslinked polyether copolymer, and furthermore, other functional groups can be introduced to make it functional. In the polyether polymer of the present invention, each Z unit may be the same or different. Therefore, the polyether polymer of the present invention may be a polymer composed of one or more units belonging to the X units and one or more units belonging to the Z units. In the polyether polymer of the present invention, each unit in the X units and each unit in the Z units are preferably the same.

[0054]

[0055] [In the formula, R] 1 Whether the same or different, it is an alkyl group with 1 to 6 carbon atoms, R 4 Same or different, for -CH2OR 8 The crosslinking group shown contains an olefinic unsaturated double bond. R 8 The same or different, being acryloyl, methacryl, allyl, or methylallyl.

[0056] R in equation (2) 1 This also includes the preferred method, and R in equation (1) 1 same.

[0057] R in equation (2) 4 In the middle, R 8 It is acryloyl, methacryloyl, allyl or methylallyl, preferably acryloyl, methacryloyl or allyl, more preferably methacryloyl or allyl, and even more preferably allyl.

[0058] The following shows a preferred embodiment of the structural unit Z derived from oxetane, represented by equation (2). The structural unit shown in equation (2-1) is preferred.

[0059]

[0060] The polyether polymer of the present invention preferably contains, in addition to the aforementioned X unit, a Y unit derived from oxetane as shown in the following general formula (3). This results in an optimized amount of X units in the polymer, improved molecular mobility, and a further increase in ionic conductivity or lithium-ion transference number.

[0061] In addition to the aforementioned X and Z units, the polyether polymer of the present invention preferably includes, in addition to the structural units derived from oxetane as shown in the following general formula (3), namely, Y units. Thus, if the structural unit is usable in the present invention, it is possible to more appropriately combine the various functions of the aforementioned X, Z, and Y units. In the polyether polymer of the present invention, each Y unit may be the same or different. Therefore, the polyether polymer of the present invention may be a polymer composed of one or more units belonging to the X unit and one or more units belonging to the Y unit. Furthermore, the polyether polymer of the present invention may be a polymer composed of one or more units belonging to the X unit, one or more units belonging to the Y unit, and one or more units belonging to the Z unit. In the polyether polymer of the present invention, each unit in the X unit, each unit in the Y unit, and each unit in the Z unit are preferably the same.

[0062]

[0063] [In the formula, R] 1 Whether the same or different, it is an alkyl group with 1 to 6 carbon atoms, R 3 Whether they are the same or different, they are hydrogen atoms or -CH2O(CH2). c (CHR 6 ) d (CH2) e R 7 The group shown. R 6 Whether the same or different, it is an alkyl group with 1 to 4 carbon atoms, R 7 The repeating units, whether the same or different, are hydrogen atoms, hydroxyl groups, nitrile groups, trifluoromethyl groups, alkoxy groups, or optionally cyclic ether groups with substituents. The number of repeating units c, whether the same or different, is an integer from 0 to 4; the number of repeating units d, whether the same or different, is an integer from 0 to 4; and the number of repeating units e, whether the same or different, is an integer from 0 to 10.

[0064] R in equation (3) 1 This also includes the preferred method, and R in equation (1) 1 same.

[0065] R as in equation (3) 3 Preferably, it is -CH2O(CH2) c (CHR 6 ) d (CH2) e R 7 The indicated group, more preferably, contains R. 6 Alkyl groups having 1 to 4 carbon atoms, R 7The group consists of hydrogen atoms, where c is an integer from 1 to 3, d is an integer from 1 to 3, and e is an integer from 1 to 8. Furthermore, more preferably, in this group, c is an integer from 1 to 3, d is an integer from 0 to 1, e is an integer from 0 to 1, and R... 7 It can be a cyclic ether group with optional substituents.

[0066] R as in equation (3) 3 R in 6 The alkyl group having 1 to 4 carbon atoms (preferably 1 to 3 carbon atoms, more preferably 1 to 2 carbon atoms) can be linear or branched, and examples include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, etc. Among them, methyl and ethyl are preferred.

[0067] R in equation (3) 3 In, as R 6 Preferably, it is an alkyl group with 1 to 4 carbon atoms.

[0068] R in equation (3) 3 In, as R 7 The alkoxy group can be, for example, an alkoxy group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms, more preferably 1 to 2 carbon atoms). This alkoxy group can be linear or branched, and examples include methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, n-pentoxy, isopentoxy, and n-hexyloxy. Among these, methoxy and ethoxy are preferred.

[0069] R in equation (3) 3 In the middle, R 7 The number of rings in the optional cyclic ether group with substituents is preferably 3 to 10, more preferably 3 to 8, and even more preferably 3 to 6.

[0070] The cyclic ether group preferably has 1 to 6 oxygen atoms, more preferably 1 to 4, and even more preferably 1 to 3.

[0071] In this specification, the ring number refers to the number of atoms that make up the framework of the ring; for example, in the case of a 5-membered ring, the ring number is 5.

[0072] Examples of substituents in cyclic ether groups include carbonyl groups, alkyl groups having 1 to 4 carbon atoms, and alkoxy groups having 1 to 4 carbon atoms. Among these, carbonyl groups and alkyl groups having 1 to 4 carbon atoms are preferred, and carbonyl groups are more preferred. As for alkyl groups having 1 to 4 carbon atoms, the substituents can be R... 6 The alkyl group having 1 to 4 carbon atoms is the same, including the preferred embodiment. Similarly, the alkyl group having 1 to 4 carbon atoms in the alkoxy group is also the same as R. 6 The alkyl groups having 1 to 4 carbon atoms are the same, including the preferred type.

[0073] R 7 The optional cyclic ether group preferably has substituents. Furthermore, the cyclic ether group preferably has a carbonate group (-O-(C=O)-O-) in the group. R is shown below. 7 The preferred method is to use cyclic ether groups with optional substituents. It should be noted that * represents a linking bond.

[0074]

[0075]

[0076] R in equation (3) 3 In, as R 7 Preferably, it contains hydrogen atoms, nitrile groups, trifluoromethyl groups, alkoxy groups, or optionally cyclic ether groups with substituents; more preferably, it contains hydrogen atoms, nitrile groups, or optionally cyclic ether groups with substituents; and even more preferably, it contains hydrogen atoms. As R 7 It is also preferred to have hydrogen atoms, nitrile groups, trifluoromethyl groups, or optional cyclic ether groups with substituents.

[0077] R in equation (3) 3 In equation (3), c is an integer from 0 to 4, preferably an integer from 1 to 3, more preferably an integer from 1 to 2, and even more preferably an integer of 1. d is an integer from 0 to 4, preferably an integer from 1 to 3, more preferably an integer from 1 to 2, and even more preferably an integer of 1. 3 In this context, e is an integer from 0 to 10, preferably an integer from 1 to 8, more preferably an integer from 2 to 6, and even more preferably an integer from 3 to 5.

[0078] The preferred R of formula (3) 1 and R 3 All of them are hydrogen atoms. As a result, the crystallinity of polyether polymers decreases, and there is a tendency to obtain better ionic conductivity.

[0079] The following shows a preferred embodiment of the Y unit, a structural unit derived from oxetane, represented by formula (3). Preferably, the structural unit is represented by formulas (3-1) to (3-6), more preferably by formulas (3-1) and (3-2), and even more preferably by formula (3-2).

[0080]

[0081]

[0082] Preferred configurations of unit X, unit Y, and unit Z are illustrated, but combinations of preferred structures of unit X and preferred structures of unit Y, combinations of preferred structures of unit X and preferred structures of unit Z, and combinations of preferred structures of unit X, preferred structures of unit Y, and preferred structures of unit Z are also preferred configurations.

[0083] In formulas (1) to (3), * represents a linking bond, which, when located at the end of the polymer, is a hydrogen atom, a hydroxyl group, or an alkoxy group.

[0084] In the polyether polymer of the present invention, the content of the X unit, which is a structural unit derived from oxetane as shown in the aforementioned general formula (1), is 20 mol% or more in 100 mol% of the structural unit. This content can be 100 mol%, preferably 20 to 99.9 mol%, more preferably 20 to 98.9 mol%. The lower limit is further preferably 30 mol% or more, particularly preferably 40 mol% or more, most preferably 50 mol% or more, even more preferably 60 mol% or more, further preferably 70 mol% or more, particularly preferably 80 mol% or more, and even more preferably 90 mol% or more. Within this range, sufficient sulfide resistance can be obtained, and there is a tendency for the lithium-ion transference number to increase.

[0085] It should be noted that in this specification, the expression "~" refers to the value above the value before the "~" and below the value after the "~".

[0086] Furthermore, in this specification, the content of unit X refers to the total content when multiple structural units are used as unit X. The same applies to other contents.

[0087] In the polyether polymer of the present invention, the content of the structural unit Z unit derived from oxobutane as shown in the aforementioned general formula (2) is preferably 0.1 to 20 mol%, more preferably 0.3 to 10 mol%, and even more preferably 0.5 to 5 mol% in 100 mol% of the structural unit. Within this range, there is a tendency to obtain sufficient mechanical strength to withstand compression, etc.

[0088] In the polyether polymer of the present invention, the content of the structural unit Y, derived from oxobutane and represented by the aforementioned general formula (3), in 100 mol% of the structural unit is preferably 1 to 79 mol%, more preferably 3 to 60 mol%, further preferably 5 to 40 mol%, particularly preferably 5 to 25 mol%, and most preferably 5 to 15 mol%. Within this range, sufficient sulfide resistance can be obtained, and there is a tendency for the lithium ion transference number to increase.

[0089] In the polyether polymer of the present invention, the total content of X unit and Z unit in 100 mol% of structural unit is preferably 80 mol% or more, more preferably 90 mol% or more, further preferably 95 mol% or more, particularly preferably 98 mol% or more, and can be 100 mol%.

[0090] In the polyether polymer of the present invention, the total content of X unit, Y unit and Z unit in 100 mol% of structural unit is preferably 80 mol% or more, more preferably 90 mol% or more, further preferably 95 mol% or more, particularly preferably 98 mol% or more, and can be 100 mol%.

[0091] In this specification, the content of each structural unit in the polyether polymer can be determined by nuclear magnetic resonance (NMR) spectroscopy of the polymer.

[0092] Without departing from the spirit of the invention, the polyether polymer of the present invention may have units other than X, Y, and Z units, such as units with thioether groups or units with sulfonyl groups. They may be used alone or in combination of two or more.

[0093] The weight-average molecular weight (Mw) of the polyether polymer of the present invention is preferably 0.5 million to 3 million, more preferably 10,000 to 2 million, and even more preferably 10,000 to 1 million. Therefore, there is a tendency to obtain the effects of the present invention more appropriately.

[0094] The dispersion (Mw / Mn) of the polyether polymer of the present invention is preferably 1 to 40, more preferably 1 to 30, further preferably 1 to 20, particularly preferably 1 to 10, and most preferably 1 to 5. Therefore, there is a tendency to obtain the effects of the present invention more appropriately.

[0095] In this specification, the weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the polymers are determined by the methods described in the examples.

[0096] The polyether polymer of the present invention can be a random copolymer, an alternating copolymer, a block copolymer, or a graft copolymer. From the perspective of disrupting the crystallinity of the polymer and obtaining a better ion transference number, a random copolymer is preferred.

[0097] The preferred embodiments of the polyether polymer of the present invention are described below.

[0098] <<Method 1-1>>

[0099] Polymers with an X unit content of 80 mol% or more

[0100] <<Method 1-2>>

[0101] Polymers containing X units and Z units, with the content of X units being 80 mol% or more.

[0102] <<Methods 1-3>>

[0103] Polymers containing X units and the following Y units

[0104] Y unit: R in equation (3) 3 -CH2O(CH2) c (CHR 6 ) d (CH2) e R 7 The group shown, in which R 6 Alkyl groups having 1 to 4 carbon atoms, R 7 For each hydrogen atom, c is an integer from 1 to 3, d is an integer from 1 to 3, and e is an integer from 1 to 8.

[0105] <Manufacturing Methods of Polyether Polymers>

[0106] Next, the monomers used in the polymerization of the polyether polymer of the present invention will be described. The X unit, Y unit, and Z unit are formed, for example, by using the compounds shown in formula (1-a), formula (3-a), and formula (2-a) as monomers, respectively.

[0107]

[0108] (In equation (1-a), R) 1 R 2 R in equation (1) 1 R 2 same.)

[0109]

[0110] (In equation (3-a), R) 1 R 3 R in equation (3) 1 R 3 same.)

[0111]

[0112] (In equation (2-a), R) 1 R 4 R in equation (2) 1 R 4 same.)

[0113] The polymerization method for the polyether polymer of the present invention is not particularly limited, and conventional polymerization reactions can be used. Anyone skilled in the art can appropriately manufacture the polyether polymer of the present invention using the above-described monomers through known polymerization methods. For example, as ring-opening polymerization catalysts, coordinating anionic initiators such as organoaluminum-based catalyst systems, organozinc-based catalyst systems, and organotin-phosphate condensate catalyst systems, and counterions containing K are used. + Anionic initiators such as potassium alkoxides, diphenylmethyl potassium, and potassium hydroxide, or cationic initiators such as boron trifluoride, diethyl ether complexes, aluminum(III), and tin(IV) chloride, which act as Lewis acids, are used to react the monomers in the presence or absence of a solvent at a reaction temperature of 0–120 °C under stirring, thereby obtaining polyether polymers.

[0114] Alternatively, the compounds shown in formula (1-a), formula (2-a), and formula (3-a) can be commercially available and, in the case of synthesis, can be obtained, for example, by reacting oxetane alcohols with haloalkyl ethers.

[0115] Polyether electrolyte for lithium-ion secondary batteries

[0116] The polyether electrolyte for lithium-ion secondary batteries of the present invention is not particularly limited as long as it contains the polyether polymer of the present invention, but preferably contains the polyether polymer of the present invention and a lithium salt compound. Here, the polyether polymer of the present invention can be used alone or in combination with two or more types.

[0117] The polyether electrolyte for lithium-ion secondary batteries of the present invention is preferably a polymeric solid electrolyte that is solid at room temperature. Furthermore, in this specification, solid electrolyte refers to an electrolyte that is solid at room temperature (does not exhibit fluidity). Here, in this specification, room temperature refers to the temperature range assumed to be the normal operating temperature range of the power supply. The upper limit of the assumed normal operating temperature range is approximately 120°C, and in some cases approximately 60°C, while the lower limit is approximately -40°C, and in some cases approximately -20°C.

[0118] In the polyether electrolyte for lithium-ion secondary batteries of the present invention, the content of the polyether polymer of the present invention is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, particularly preferably 95% by mass or more, and can be 100% by mass. Therefore, there is a tendency to obtain the effects of the present invention more appropriately.

[0119] In this specification, the content of each polymer can be determined by nuclear magnetic resonance spectroscopy.

[0120] As lithium salt compounds, lithium salt compounds with a wide potential window commonly used in lithium-ion batteries are preferred. Examples of lithium salt compounds include LiBF4, LiPF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiN(CF3SO2)2(LiTFSI), LiN(SFO2)2(LiFSI), LiN(C2F5SO2)2, and LiN[CF3SC(C2F5SO2)3]2. They can be used alone or in combination of two or more.

[0121] When the polyether electrolyte for lithium-ion secondary batteries of the present invention contains a lithium salt compound, the content of the lithium salt compound is preferably 5 to 300 parts by mass, more preferably 5 to 200 parts by mass, and even more preferably 5 to 100 parts by mass, relative to 100 parts by mass of the polyether polymer (preferably the polyether polymer of the present invention). Therefore, there is a tendency to obtain the effects of the present invention more appropriately.

[0122] In the polyether electrolyte for lithium-ion secondary batteries of the present invention, the total content of the polyether polymer and lithium salt compound in 100% by mass of the polyether electrolyte for lithium-ion secondary batteries of the present invention is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, particularly preferably 95% by mass or more, and may also be 100% by mass. Therefore, there is a tendency to obtain the effects of the present invention more appropriately.

[0123] The polyether electrolyte for lithium-ion secondary batteries of the present invention may contain a room-temperature molten salt. A room-temperature molten salt refers to a salt that is at least partially liquid at room temperature.

[0124] Molten salts at room temperature are also known as ionic liquids, including quaternary ammonium organic cations such as pyridine-based, aliphatic amine-based, and alicyclic amine-based cations. They can be used alone or in combination of two or more. Examples of quaternary ammonium organic cations include dialkylimidazolium, trialkylimidazolium, tetraalkylammonium, alkylpyridinium, pyrazolium, pyrrolidine, and piperidinium ions.

[0125] The polyether electrolyte for lithium-ion secondary batteries of the present invention may contain a plasticizer. There are no particular limitations on the plasticizer, but dicyano compounds and branched ether compounds are preferred. They can be used alone or in combination of two or more. When the polyether electrolyte for lithium-ion secondary batteries of the present invention contains a plasticizer, it is preferable to crosslink the polyether polymer of the present invention after mixing the plasticizer. This helps to suppress the leaching of the plasticizer.

[0126] In addition to the components described above, the polyether electrolyte for lithium-ion secondary batteries of the present invention may also include, for example, reaction initiators, crosslinking aids, and binders. These can be used individually or in combination of two or more. The reaction initiators and crosslinking aids will be described in detail in the description of the crosslinked film. It should be noted that the polyether electrolyte for lithium-ion secondary batteries of the present invention may or may not be crosslinked.

[0127] The polyether electrolyte for lithium-ion secondary batteries of the present invention can be prepared using conventionally known methods, for example, by adding lithium salt compounds or the like to the polyether polymer of the present invention as needed and mixing them. Alternatively, drying may be performed as needed.

[0128] <Composite Solid Electrolyte for Lithium-ion Secondary Batteries>

[0129] The composite solid electrolyte for lithium-ion secondary batteries of the present invention (sometimes simply referred to as composite solid electrolyte) comprises an inorganic solid electrolyte and a polyether electrolyte for lithium-ion secondary batteries of the present invention (the polyether polymer of the present invention). In addition to the inorganic solid electrolyte, the composite solid electrolyte of the present invention also contains the polyether electrolyte for lithium-ion secondary batteries of the present invention (the polyether polymer of the present invention). Therefore, compared to cases where a solid electrolyte is formed solely from an inorganic solid electrolyte, the contact area at the interface between the electrode material layer and the solid electrolyte layer is considered to be large. As a result, the interfacial resistance between the electrode and the electrolyte is reduced, leading to excellent charge-discharge characteristics. Furthermore, it is believed that in the composite solid electrolyte, the polyether electrolyte for lithium-ion secondary batteries of the present invention (the polyether polymer of the present invention) reduces the internal resistance of the composite solid electrolyte by tightly binding the particles of the inorganic solid electrolyte. Here, the polyether electrolyte for lithium-ion secondary batteries of the present invention (the polyether polymer of the present invention) can be used alone or in combination of two or more types.

[0130] Examples of inorganic solid electrolytes include oxide-based solid electrolytes and sulfide-based solid electrolytes. They can be used alone or in combination of two or more. In the composite solid electrolyte of the present invention, the inorganic solid electrolyte is contained, for example, in particulate form, and has a structure in which the particles of the inorganic solid electrolyte are tightly bound together by the polyether electrolyte for lithium-ion secondary batteries of the present invention (the polyether polymer of the present invention).

[0131] There are no particular restrictions on oxide-based solid electrolytes as long as they contain oxygen, have the ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table, and have electronic insulation.

[0132] Li can be cited as a specific compound constituting an oxide-based solid electrolyte. x La yTiO3 [x=0.3~0.7, y=0.3~0.7] (LLT), Li x La y Zr z M m O n (M is at least one element selected from Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, x satisfies 5 ≤ ​​x ≤ 10, y satisfies 1 ≤ y ≤ 4, z satisfies 1 ≤ z ≤ 4, m satisfies 0 ≤ m ≤ 2, and n satisfies 5 ≤ ​​n ≤ 20), Li x B y M z O n (In the formula, M is at least one element selected from C, S, Al, Si, Ga, Ge, In, and Sn, x satisfies 0 ≤ x ≤ 5, y satisfies 0 ≤ y ≤ 1, z satisfies 0 ≤ z ≤ 1, and n satisfies 0 ≤ n ≤ 6), Li x (Al, Ga) y (Ti, Ge) z Si a P m O n (where 1≤x≤3, 0≤y≤1, 0≤z≤2, 0≤a≤1, 1≤m≤7, 3≤n≤13), Li (3-2x) M x DO (x represents a number greater than 0 and less than 0.1, M represents a divalent metal atom, and D represents a halogen atom or a combination of two or more halogen atoms), Li x Si y O z (1≤x≤5, 0<y≤3, 1≤z≤10), Li x S y O z (1≤x≤3, 0<y≤2, 1≤z≤10), Li3BO3-Li2SO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li6BaLa2Ta2O 12 Li3PO (4-3 / 2w) N w (w is w < 1), Li with a LISICON (Lithium superionic conductor) type crystal structure 3.5 Zn 0.25 GeO4, La with a perovskite-type crystal structure 0.55 Li 0.35 TiO3 and LiTi2P3O, which have a NASICON (Natrium superionic conductor) crystal structure. 12 Li(1+x+y) (Al, Ga) x (Ti, Ge) (2-x) Si y P (3-y) O 12 (Where 0≤x≤1, 0≤y≤1), and Li7La3Zr2O12 having a garnet-type crystal structure, etc. Furthermore, phosphorus compounds containing Li, P, and O are preferred. Examples include lithium phosphate (Li3PO4), LiPON (where a portion of the oxygen in lithium phosphate is replaced by nitrogen), and LiPOD (where D is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc.). Additionally, LiAON (where A is at least one selected from Si, B, Ge, Al, C, Ga, etc.) is also preferred.

[0133] Among them, Li is preferred. x La y TiO3[x=0.3~0.7, y=0.3~0.7](LLT), Li x La y Zr z M m O n (M is at least one of the elements Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, x satisfies 5 ≤ ​​x ≤ 10, y satisfies 1 ≤ y ≤ 4, z satisfies 1 ≤ z ≤ 4, m satisfies 0 ≤ m ≤ 2, and n satisfies 5 ≤ ​​n ≤ 20), Li7La3Zr2O 12 (LLZ), Li3BO3, Li3BO3-Li2SO4, Li3BO3-Li2CO3, Li x (Al,Ga) y (Ti,Ge) z Si a P m O n (Where, 1≤x≤3, 0≤y≤1, 0≤z≤2, 0≤a≤1, 1≤m≤7, 3≤n≤13).

[0134] There are no particular restrictions on sulfide-based solid electrolytes as long as they contain sulfur, have the ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table, and have electronic insulation properties.

[0135] Sulfide-based solid electrolytes can be either glass-based or glass-ceramic-based. They can be used alone or in combination of two or more. Glass-based solid electrolytes are obtained by vitrifying the raw materials. Glass-ceramic-based solid electrolytes can be obtained, for example, by heat-treating glass-based solid electrolytes. Furthermore, sulfide-based solid electrolytes preferably have a crystalline structure. Examples of crystalline structures include the Thio-LISICON type, the LGPS type, and the argentite-germanium sulfide type.

[0136] Examples of glassy sulfide solid electrolytes include Li₂S-P₂S₅, Li₂S-LiI-P₂S₅, Li₂S-LiI-Li₂O-P₂S₅, Li₂S-LiBr-P₂S₅, Li₂S-Li₂O-P₂S₅, Li₂S-Li₃PO₄-P₂S₅-P₂O₅, Li₂S-P₂S₅-SiS₂, Li₂S-P₂S₅-SnS, Li₂S-P₂S₅-Al₂S₃, Li₂S-GeS₂, and Li₂S-GeS₂-ZnS. These can be used individually or in combination of two or more.

[0137] As a sulfide-based solid electrolyte with a crystalline structure, Li can be cited as an example. 10 GeP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 Li 9.42 Si 1.02 P 2.1 S 9.96 O 2.24 LGPS type sulfide solid electrolyte, Li6PS5Cl, Li 6.6 Ge 0.6 P 0.4 S5I, Li7Ge3PS 12 Iso-silver-germanium sulfide solid electrolyte, Li 4.275 Ge 0.61 Ga 0.25 Thio-LISICON type sulfide solid electrolytes include S4, Li4SnS4, and β-Li3PS4. Among these, thio-LISICON type sulfide solid electrolytes and thio-LISICON type sulfide solid electrolytes are preferred, with thio-LISICON type sulfide solid electrolytes being more preferred. They can be used alone or in combination of two or more types.

[0138] From the perspective of improving the electrical properties of all-solid-state lithium-ion secondary batteries, sulfide-based solid electrolytes are preferably sulfide-based solid electrolytes with high ionic conductivity. Specifically, an ionic conductivity of 1×10⁻⁶ is preferred. -4 S / cm or higher, more preferably 1×10 -3 S / cm or higher.

[0139] As an inorganic solid electrolyte, a sulfide-based solid electrolyte is preferred. The polyether polymer of the present invention can suppress side reactions with the sulfide-based solid electrolyte and has a high ion transference number, thus allowing the effects of the present invention to be more appropriately realized.

[0140] When the inorganic solid electrolyte is in particulate form, its particle size can be, for example, 0.01 to 100 μm, preferably 0.1 to 20 μm.

[0141] In the composite solid electrolyte for lithium-ion secondary batteries of the present invention, the mass ratio of the inorganic solid electrolyte to the polyether electrolyte for lithium-ion secondary batteries of the present invention (preferably the polyether polymer of the present invention) is not particularly limited. From the viewpoint of enabling the secondary battery to more appropriately exhibit excellent charge and discharge characteristics, the content of the polyether electrolyte for lithium-ion secondary batteries of the present invention (preferably the polyether polymer of the present invention) is preferably 0.1 to 1000 parts by mass relative to 100 parts by mass of the inorganic solid electrolyte, more preferably 0.5 to 800 parts by mass, further preferably 5 to 600 parts by mass, and particularly preferably 10 to 400 parts by mass.

[0142] In the composite solid electrolyte for lithium-ion secondary batteries of the present invention, the total content of the inorganic solid electrolyte and the polyether electrolyte for lithium-ion secondary batteries of the present invention in 100% by mass is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, particularly preferably 95% by mass or more, and may also be 100% by mass. Therefore, there is a tendency to obtain the effects of the present invention more appropriately.

[0143] The composite solid electrolyte for lithium-ion secondary batteries of the present invention includes not only an inorganic solid electrolyte but also a polyether electrolyte for lithium-ion secondary batteries, thus, unlike the case where only an inorganic solid electrolyte is used, it can also be suitably molded into a sheet shape. There are no particular limitations on the thickness when the composite solid electrolyte of the present invention is applied to a secondary battery; for example, a thickness of about 0.01 to 1 mm is possible, and preferably about 0.05 to 0.3 mm.

[0144] In addition to the polyether electrolyte for lithium-ion secondary batteries of the present invention, the composite solid electrolyte for lithium-ion secondary batteries of the present invention may also include, for example, reaction initiators, crosslinking aids, binders, etc. These can be used individually or in combination of two or more.

[0145] The composite solid electrolyte for lithium-ion secondary batteries of the present invention can be prepared using conventionally known methods, such as by mixing an inorganic solid electrolyte with the polyether electrolyte for lithium-ion secondary batteries of the present invention (the polyether polymer of the present invention). Specifically, it can be manufactured by methods such as: dispersing an inorganic solid electrolyte in a solvent containing the polyether electrolyte for lithium-ion secondary batteries of the present invention (the polyether polymer of the present invention) to prepare a composite solid electrolyte slurry; spraying and drying the slurry in hot air to obtain the composite solid electrolyte; heating and evaporating the solvent of the dispersion slurry under atmospheric pressure or reduced pressure to dry and solidify it; coating the dispersion slurry onto a current collector sheet or the like and drying it; etc.

[0146] As a dispersion solvent, water, organic solvents, and mixtures thereof in any ratio can be used. Whether the resulting dispersion slurry is a homogeneous solution, or the inorganic solid electrolyte and / or the polyether electrolyte for lithium-ion secondary batteries of the present invention is a solute existing in a form insoluble in the dispersion solvent, it can be prepared by the conventional preparation method described above. The composite solid electrolyte obtained by removing the dispersion solvent preferably has as much residual solvent and water as possible removed. For example, this can be achieved by vacuum degassing at heating at 30°C to 200°C for 1 to 48 hours. The dried composite solid electrolyte of the present invention, in addition to having a high ion mobility number, also has adhesive properties, thus allowing the electrolyte powder to be self-pressurized and used as a solid electrolyte material. Furthermore, by performing pressure heat treatment, the porosity can be reduced and the interparticle interface tightness increased. As an organic solvent, a polar solvent is preferred. Specifically, acetonitrile, ethanol, methanol, tetrahydrofuran, dimethylformamide, dimethyl sulfoxide, dioxane, methyl ethyl ketone, methyl isobutyl ketone, etc., can be used alone or in combination. If inorganic solid electrolytes are pressurized separately, a thick film electrolyte will be formed due to the lack of adhesion. However, in composite solid electrolytes, thanks to the adhesion of the polyether electrolyte for lithium-ion secondary batteries (the polyether polymer of the present invention), a thinner solid electrolyte can be manufactured.

[0147] The composite solid electrolyte of the present invention may or may not be cross-linked, but cross-linking is preferred. By cross-linking, the composite solid electrolyte of the present invention can further improve the bonding strength between the inorganic solid electrolyte within the composite solid electrolyte and the polyether electrolyte for lithium-ion secondary batteries of the present invention (the polyether polymer of the present invention). In addition, it can more effectively prevent short circuits in the battery caused by confinement pressure and dendrite precipitation. As a cross-linking method, cross-linking can be performed by heating or irradiation with active energy rays such as ultraviolet light.

[0148] When crosslinking is performed using heat, a free radical initiator selected from organic peroxides, azo compounds, etc., is used. These can be used alone or in combination of two or more. As organic peroxides, ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxide esters, and other organic peroxides commonly used for crosslinking applications can be used. As azo compounds, azo nitrile compounds, azo amide compounds, azomididine compounds, and other azo compounds commonly used for crosslinking applications can be used. The amount of free radical initiator added varies depending on the type; generally, when the polyether polymer (ion-conducting polymer) is set at 100 parts by weight, it is in the range of 0.1 to 10 parts by weight.

[0149] As free radical initiators for crosslinking under irradiation with active energy rays, alkyl phenyl ketones, benzophenones, acylphosphine oxides, dicenecenes, triazines, diimidazoles, and oxime esters can be used. They can be used alone or in combination of two or more. The amount of these free radical polymerization initiators added varies depending on the type; typically, when the polyether polymer (ion-conducting polymer) is set at 100 parts by weight, the amount is in the range of 0.01 to 5.0 parts by weight.

[0150] When crosslinking composite solid electrolytes, crosslinking aids can be used as needed. Common crosslinking aids include ethylene glycol diacrylate, ethylene glycol dimethacrylate, oligomeric polyethylene glycol diacrylate, oligomeric polyethylene glycol dimethacrylate, trimethylolpropane triacrylate, allyl methacrylate, allyl acrylate, diallyl maleate, triallyl isocyanurate, maleimide, phenylmaleimide, maleic anhydride, pentaerythritol tetra(3-mercaptobutyrate), and 1,4-bis(3-mercaptobutyryloxy)butane. These can be used alone or in combination of two or more.

[0151] Lithium-ion secondary batteries

[0152] The lithium-ion secondary battery of the present invention is a lithium-ion secondary battery that uses the polyether electrolyte for lithium-ion secondary batteries of the present invention. There are no particular limitations on the lithium-ion secondary battery of the present invention as long as it uses the polyether electrolyte for lithium-ion secondary batteries of the present invention. Preferably, it is a lithium-ion secondary battery that uses the composite solid electrolyte for lithium-ion secondary batteries of the present invention. As a stacked structure of the secondary battery, for example, there is a stacked structure in which a positive electrode, a solid electrolyte layer, and a negative electrode are stacked sequentially; as the solid electrolyte layer, the composite solid electrolyte for lithium-ion secondary batteries of the present invention is preferably used.

[0153] Cross-linked Films

[0154] In the secondary battery of the present invention, a cross-linked film of the polyether electrolyte for lithium-ion secondary batteries of the present invention can be disposed between at least one of the positive electrode and the solid electrolyte layer, and between the negative electrode and the solid electrolyte layer. By disposing of this cross-linked film, the interfacial resistance between the electrode and the solid electrolyte layer can be further reduced.

[0155] The crosslinked film is preferably formed by crosslinking at least a composition comprising a lithium salt compound and the polyether polymer of the present invention, i.e., the polyether electrolyte for lithium-ion secondary batteries of the present invention. That is, the crosslinked film is a crosslinked film comprising a composition comprising a lithium salt compound and the polyether polymer of the present invention. The polyether polymer of the present invention and the polyether electrolyte for lithium-ion secondary batteries of the present invention are as described above.

[0156] A cross-linked film can also be formed by mixing a reaction initiator and a cross-linking aid into the polyether electrolyte for lithium-ion secondary batteries of the present invention. Examples of reaction initiators include thermal reaction initiators and photoreaction initiators. They can be used alone or in combination of two or more.

[0157] As the thermal reaction initiator, a free radical initiator selected from organic peroxides, azo compounds, etc., is used. As the organic peroxide, ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxide esters, and other organic peroxides commonly used for crosslinking applications can be used. As the azo compound, azo nitrile compounds, azo amide compounds, azomididine compounds, and other azo compounds commonly used for crosslinking applications can be used. The amount of free radical initiator added varies depending on the type; generally, when the ion-conducting polymer is set at 100 parts by weight, it is in the range of 0.1 to 10 parts by weight.

[0158] As photoreaction initiators, free radical initiators such as alkyl phenyl ketones, benzophenones, acylphosphine oxides, dicenecenes, triazines, diimidazoles, and oxime esters can be used. The amount of these free radical polymerization initiators added varies depending on the type; typically, when the ion-conducting polymer is set to 100 parts by weight, the amount is in the range of 0.01 to 5.0 parts by weight.

[0159] As crosslinking aids, ethylene glycol diacrylate, ethylene glycol dimethacrylate, oligomeric polyethylene glycol diacrylate, oligomeric polyethylene glycol dimethacrylate, trimethylolpropane triacrylate, allyl methacrylate, allyl acrylate, diallyl maleate, triallyl isocyanurate, maleimide, phenylmaleimide, maleic anhydride, pentaerythritol tetra(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, etc., can be used arbitrarily. They can be used alone or in combination of two or more.

[0160] The polyether electrolyte for lithium-ion secondary batteries of the present invention can be mixed with organic solvents. Examples of organic solvents include toluene, xylene, benzene, acetonitrile, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and THF (tetrahydrofuran). They can be used alone or in combination of two or more.

[0161] Examples of methods for producing cross-linked films include: mixing and dissolving the lithium-ion secondary battery polyether electrolyte of the present invention in an organic solvent to form a composition; casting the composition on a substrate (e.g., PET film, Teflon sheet, etc.); removing the solvent; and then producing a cross-linked film by heating or irradiation with active energy rays such as ultraviolet light. Alternatively, the composition can be cast directly onto the surface of a solid electrolyte layer to produce a cross-linked film.

[0162] The thickness of the crosslinked film is preferably 0.1 μm to 200 μm, more preferably in the range of 0.5 μm to 100 μm.

[0163] In the secondary battery of the present invention, the crosslinked film is preferably a crosslinked film using the polyether electrolyte for lithium-ion secondary batteries of the present invention, but the crosslinked film may also be a crosslinked film using a "composition containing an ion-conducting polymer containing a lithium salt compound" other than the polyether electrolyte for lithium-ion secondary batteries of the present invention.

[0164] <<The specific composition of lithium-ion secondary batteries, etc.>>

[0165] Examples of the stacked structures for the secondary battery of the present invention include the following. Furthermore, the composite solid electrolyte for lithium-ion secondary batteries of the present invention is preferably used as the solid electrolyte layer. Additionally, the crosslinked film is preferably a crosslinked film using the polyether electrolyte for lithium-ion secondary batteries of the present invention.

[0166] A stacked structure consisting of a positive electrode, a solid electrolyte layer, and a negative electrode stacked sequentially;

[0167] A stacked structure consisting of a positive electrode, a cross-linked film, a solid electrolyte layer, another cross-linked film, and a negative electrode stacked sequentially;

[0168] A stacked structure consisting of a positive electrode, a solid electrolyte layer, a cross-linked film, another solid electrolyte layer, and a negative electrode stacked sequentially.

[0169] A stacked structure consisting of a positive electrode, a cross-linked film, a solid electrolyte layer, and a negative electrode stacked sequentially;

[0170] A stacked structure consisting of a positive electrode, a solid electrolyte layer, a cross-linked film, and a negative electrode stacked sequentially.

[0171] In the secondary battery of the present invention, it is preferable that the solid electrolyte layer is in contact with a cross-linked film using the polyether electrolyte for lithium-ion secondary batteries of the present invention. The cross-linked film is a cross-linked body of the polyether electrolyte for lithium-ion secondary batteries of the present invention, and therefore has a high ion mobility number and high flexibility compared to inorganic materials. Therefore, it is considered that the contact area between the cross-linked film and the solid electrolyte layer is increased, resulting in an effective reduction in the interfacial resistance of the solid electrolyte layer, and the secondary battery of the present invention exhibits excellent charge-discharge characteristics. It should be noted that in the secondary battery of the present invention, it is also preferable that the cross-linked film is in contact with the electrode material layer of the electrode, and even more preferably, that the cross-linked film is in contact with both the electrode material layer and the solid electrolyte layer.

[0172] The secondary battery of the present invention comprises at least a positive electrode, a negative electrode, and a solid electrolyte layer. As mentioned above, the composite solid electrolyte for lithium-ion secondary batteries of the present invention is preferably used as the solid electrolyte layer. Furthermore, as described above, when the secondary battery of the present invention comprises a crosslinked film, a crosslinked film utilizing the polyether electrolyte for lithium-ion secondary batteries of the present invention is preferably used as the crosslinked film.

[0173] Both the positive and negative electrodes can be made of known materials. Examples include electrodes having an electrode material layer, i.e., a positive electrode material layer or a negative electrode material layer, on the current collector.

[0174] Both the positive and negative electrodes can use known current collectors. Specifically, the positive electrode uses metals such as aluminum, nickel, stainless steel, gold, platinum, and titanium as current collectors. The negative electrode uses metals such as copper, nickel, stainless steel, gold, platinum, and titanium as current collectors.

[0175] In addition, the positive electrode material layer and the negative electrode material layer respectively contain at least positive electrode active material and negative electrode active material, and may also contain conductive additives, binders, thickeners, and may also contain the above-mentioned inorganic solid electrolyte or the composite solid electrolyte for lithium-ion secondary batteries of the present invention as needed.

[0176] The positive electrode active material used in this invention is a lithium-containing metal composite oxide powder comprising any composition of LiMO2, LiM2O4, Li2MO3, and LiMEO4. Here, M in the formula is mainly composed of transition metals, including at least one of Co, Mn, Ni, Cr, Fe, and Ti. Besides transition metals, Al, Ga, Ge, Sn, Pb, Sb, Bi, Si, P, and B may also be added. E includes at least one of P and Si. The particle size of the positive electrode active material is preferably 50 μm or less, more preferably 20 μm or less. These active materials have an electromotive force of 3V (vs. Li / Li+) or higher.

[0177] Specific examples of positive electrode active materials include lithium cobalt oxide, lithium nickel oxide, lithium nickel / cobalt / manganese oxide (ternary system), spinel-type lithium manganese oxide, and lithium iron phosphate.

[0178] The negative electrode active material used in this invention is a carbon material (natural graphite, artificial graphite, amorphous carbon, etc.) having a structure (interlayer compound) capable of absorbing / releasing alkali metal ions such as lithium ions, or a metal such as lithium, aluminum-based compounds, tin-based compounds, silicon-based compounds, titanium-based compounds, etc., capable of absorbing / releasing alkali metal ions such as lithium ions. In the case of a powder, the particle size is preferably 10 nm or more and 100 μm or less, more preferably 20 nm or more and 20 μm or less. Alternatively, it can also be used in the form of a mixed active material of metal and carbon.

[0179] When using conductive additives, known conductive additives can be used, such as conductive carbon blacks like graphite, furnace black, acetylene black, and Ketjen black, carbon fibers like carbon nanotubes, or metal powders. One or more of these conductive additives can be used.

[0180] As a binder, one or more compounds selected from fluoropolymers such as PVdF, fluororubber, acrylate rubber, modified acrylate rubber, styrene-butadiene rubber, acrylic polymers, and vinyl polymers can be used. When the active material is set to 100 parts by mass, these binders are preferably added at 5 parts by mass or less, more preferably at 3 parts by mass or less, for example, 0.01 to 2 parts by mass.

[0181] Specific examples of thickeners include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose and their salts (alkali metal salts such as sodium salts, ammonium salts), polyvinyl alcohol, polyacrylate, polyethylene oxide, etc. One or more of these thickeners can be used. When the active substance is set at 100 parts by mass, it is preferable to add 5 parts by mass or less, more preferably 3 parts by mass or less, for example, 0.01 to 2 parts by mass. Furthermore, when the viscosity of the coating liquid is low, thickeners can be used in combination.

[0182] There are no particular limitations on the manufacturing methods for the positive and negative electrodes, which have current collectors and positive and negative electrode material layers, and general methods can be used. For example, a paste (coating solution) containing positive or negative electrode active material, conductive additive, binder, water or solvent such as N-methyl-2-pyrrolidone (NMP), and a thickener as needed, is uniformly coated onto the surface of the current collector at an appropriate thickness using a doctor blade method, screen printing method, or similar methods.

[0183] For example, in the doctor blade method, negative electrode active material powder, positive electrode active material powder, conductive additives, binders, etc., are dispersed in water to form a slurry. This slurry is then coated onto a metal electrode substrate, and a doctor blade with a specified slit width is used to homogenize it to an appropriate thickness. After the active material is coated, the electrode is dried, for example, under hot air at 100°C and reduced pressure at 80°C, to remove excess organic solvent. The dried electrode is then pressed into shape using a pressing device to manufacture the electrode.

[0184] The manufacturing method of the secondary battery of the present invention is not particularly limited, but it consists of at least a positive electrode, a negative electrode, and a solid electrolyte, and is manufactured by a known method. For example, in the case of a coin-shaped lithium-ion battery, the positive electrode, solid electrolyte, and negative electrode are inserted into an outer can. Then, they are joined to a sealing body by means of electrode tab welding or the like, sealed into the sealing body, and riveted to obtain a battery. The shape of the battery is not limited; examples include coin-shaped, cylindrical, and sheet-shaped batteries, and it can also be a structure formed by stacking two or more batteries.

[0185] The secondary battery of the present invention is preferably an all-solid-state battery. Therefore, it is possible to manufacture a secondary battery with higher safety.

[0186] The polyether polymer of the present invention, the polyether electrolyte for lithium-ion secondary batteries using the polyether polymer, the composite solid electrolyte for lithium-ion secondary batteries, and the lithium-ion secondary batteries can suppress side reactions with sulfide-based solid electrolytes and have high ion mobility numbers. Therefore, they are useful in batteries for electric vehicles, hybrid vehicles, and other vehicles, batteries for household power storage, batteries for electronic devices such as mobile phones and personal computers.

[0187] Example

[0188] The present invention will be specifically described through examples and comparative examples. However, the present invention is not limited to these.

[0189] [Manufacturing Example 1-1] (Synthesis of Cyclic Ether Compound 1)

[0190] 320 parts by mass of 3-ethyl-3-oxetane-methanol and 694 parts by mass of potassium hydroxide were added to a flask along with solvent, and the mixture was stirred at room temperature for 1 hour. The reaction solution was cooled to 10°C, and 967 parts by mass (2.1 equivalents) of 1-bromo-4-methoxybutane were added dropwise while stirring. After the addition was complete, the reaction was allowed to proceed for 44 hours. Then, an oil-water separation operation was performed, and the resulting organic layer was concentrated to obtain 420 parts by mass of cyclic ether compound 1.

[0191] [Manufacturing Examples 1-2] (Synthesis of Cyclic Ether Compound 2)

[0192] Except for replacing 1-bromo-4-methoxybutane with 1-bromo-3-methoxypropane, the same procedure as in Manufacturing Example 1-1 was carried out to obtain cyclic ether compound 2.

[0193] [Manufacturing Examples 1-3] (Synthesis of Cyclic Ether Compound 3)

[0194] Except for replacing 1-bromo-4-methoxybutane with 2-bromoethylmethyl ether, the same procedure as in Manufacturing Example 1-1 was performed to obtain cyclic ether compound 3.

[0195] [Manufacturing Examples 1-4] (Synthesis of Cyclic Ether Compound 4)

[0196] Except for replacing 1-bromo-4-methoxybutane with allyl bromide, the process was carried out in the same manner as in Manufacturing Example 1-1 to obtain cyclic ether compound 4.

[0197] [Manufacturing Examples 1-5] (Synthesis of Cyclic Ether Compound 5)

[0198] Except for replacing 1-bromo-4-methoxybutane with 2-ethylhexyl chloride, the same procedure as in Manufacturing Example 1-1 was performed to obtain cyclic ether compound 5.

[0199] [Manufacturing Examples 1-6] (Synthesis of Cyclic Ether Compound 6)

[0200] 100 parts by weight of 3-ethyl-3-oxetane glycidyl ether and 14.8 parts by weight of diazabicycloundecene hydroiodate were added to a flask. While bubbling with 25.6 parts by weight of carbon dioxide at a flow rate of 30-50 mL / min, the mixture was stirred at 45°C for 18 hours. Then, oil-water separation was performed, and the resulting organic layer was concentrated and purified by silica gel column chromatography to obtain 108 parts by weight of cyclic ether compound 6.

[0201] [Manufacturing Examples 1-7] (Synthesis of Cyclic Ether Compound 7)

[0202] Except for replacing 1-bromo-4-methoxybutane with 2-bromo-1-methoxypropane, the same procedure as in Manufacturing Example 1-1 was performed to obtain cyclic ether compound 7.

[0203] [Manufacturing Examples 1-8] (Synthesis of Cyclic Ether Compound 8)

[0204] Except for replacing 1-bromo-4-methoxybutane with 1,1,1-trifluoro-2-iodoethane, the process was carried out in the same manner as in Manufacturing Example 1-1 to obtain cyclic ether compound 8.

[0205] The structural and chemical structure identification results (NMR) of the obtained cyclic ether compounds are summarized below.

[0206]

[0207]

[0208]

[0209]

[0210]

[0211]

[0212]

[0213]

[0214] [Example 1] (Polyether polymer 1)

[0215] 100 parts by mass of cyclic ether compound 1 (component X of the polyether polymer) and 1,2-dichloroethane as solvent were added, and the mixture was cooled to 0°C while stirring. While maintaining the temperature, 1.6 parts by mass of BF3·Et2O were added over 5 minutes as a polymerization initiator, bringing the total to 2 mol% of the polyether polymer composition. The polymerization reaction was further carried out for 2 hours. A 4M NaCl / 1M NaOH aqueous solution was added to stop the reaction, and oil-water separation was performed. Then, purification based on reprecipitation and vacuum drying at 50°C were performed to obtain polyether polymer 1. The following experiments were conducted using the obtained polyether polymer 1, and the results are shown in Table 1.

[0216] The weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the obtained polyether polymers were determined. The results are shown in Table 1. It should be noted that the content of each unit shown in Table 1 was calculated by NMR spectroscopy.

[0217] <Weight-average molecular weight (Mw), Number-average molecular weight (Mn)>

[0218] The polymer was dissolved in tetrahydrofuran (THF) as a solvent, and the molecular weight was determined by gel permeation chromatography (GPC) using polystyrene conversion. The weight-average molecular weight (Mw) and number-average molecular weight (Mn) were calculated based on the results. For the determination, a Shimadzu LC-2030 (RID-20A) column and three Resonac Corporation GPC columns (KF-801, KF-803L, and KF-806L) were used. The flow rate was set to 1.0 mL / min, the concentration was set to 10 mg polymer / 8 mL THF, and the determination was performed at an injection volume of 100 μL and a column temperature of 40 °C.

[0219] [Degradation Evaluation of Sulfide Solid Electrolytes]

[0220] The polyether polymer 1 was dissolved in toluene at a solid content concentration of 10% by mass to prepare polyether solution 1. 0.4 parts by mass of a sulfide solid electrolyte (Li6PS5Cl, manufactured by NEI) and 1.0 parts by mass of polyether solution 1 (polyether: 0.1 parts by mass) were added and mixed. The solvent was removed by vacuum heating to prepare a composite 1 of the sulfide solid electrolyte and polymer. This composite 1 was filled into a solid NMR sample tube and subjected to a heat treatment at 60°C for 1 week, followed by NMR analysis. 31 P-NMR test.

[0221] ( 31 P-NMR test)

[0222] The measurements were performed using an NMR apparatus (ECA400WB, manufactured by NEC Corporation). As an evaluation method, the PS4 content in the sulfide solid electrolyte was considered. 3- The spectrum of the unit source and P2S7 generated through the decomposition reaction of sulfide solid electrolytes. 4- The presence or absence of spectra from the unit source is used to evaluate tolerance. A value of 0 is assigned to cases where no spectra generated by the decomposition reaction of sulfide solid electrolytes are detected, and a value of × is assigned to cases where spectra generated by the decomposition reaction of sulfide solid electrolytes are detected. A value of 0 indicates that side reactions with sulfide-based solid electrolytes can be suppressed.

[0223] Measurement temperature: room temperature

[0224] Rotation speed: 10kHz

[0225] Total number of times: 8

[0226] Repeat wait time: 2,000 seconds

[0227] Standard reference for chemical shift: Ammonium dihydrogen phosphate (1 ppm)

[0228] [Evaluation of Li ion transport number in polyether electrolytes]

[0229] (Evaluating the battery's manufacturing process)

[0230] 100 parts by weight of the polyether polymer 1 obtained above and 25.5 parts by weight of Li(CF3SO2)2N as a lithium salt compound were mixed, and the oxygen to lithium ratio ([Li] / [O]) in the polyether polymer was 0.06 during mixing to obtain polyether electrolyte 1. Polyether electrolyte 1 was dissolved in tetrahydrofuran to a solid content concentration of 10% by weight to prepare polyether electrolyte solution 1. Polyether electrolyte solution 1 was coated onto a nonwoven fabric separator and dried to prepare a polyether electrolyte membrane 1 containing the separator (electrolyte membrane thickness: 100 μm). Then, the polyether electrolyte membrane 1 containing the separator was clamped using Li foil to fabricate a Li symmetric cell.

[0231] (Calculation of Li ion transference number)

[0232] The Li ion transport number can be calculated using the interfacial resistance values ​​before and after polarization, the initial current value obtained from the chronoamperometric test, and the steady-state current value, by the following formula.

[0233] t Li+ =(I s ×(V-I0×R0)) / ((I0×(VI s ×R s )))

[0234] t Li+ Li ion transference number of polyether electrolytes

[0235] I0: Initial current value (A) for the chronoamperometric test.

[0236] I s Steady-state current value (A) of the chronoamperometric test.

[0237] R0: Interface resistance before polarization (Ω)

[0238] R s : Interfacial resistance after polarization (Ω)

[0239] V: DC voltage (V)

[0240] (Measurement of interfacial resistance before and after polarization (AC impedance test))

[0241] A Li-symmetric cell with polyether electrolyte was fabricated, and AC impedance testing was conducted using a potentiostat / galvanostat. The interfacial resistance was calculated based on the size of the semicircular arc derived from the interfacial resistance from the Cole-Cole curve. The test temperature was set at 25°C, and measurements were performed at a voltage amplitude of 20mV and a frequency range of 7MHz to 100mHz.

[0242] (Time-amplitude ampere method test)

[0243] After performing the AC impedance test, the open-circuit voltage (OCV) was measured for 1 minute, followed by the chronoamperometry method.

[0244] The test temperature was set at 25℃. The measurement was conducted with a DC voltage of 20mV for 3 hours, measuring the initial current value and the steady-state current value after 3 hours.

[0245] [Examples 2-10, Comparative Examples 1-3] (Polyether polymers 2-13)

[0246] The addition time of the polymerization initiator was changed to 10 minutes, and the process was otherwise the same as in Example 1, to obtain polyether polymer 2. The composition was changed to that shown in Table 1, and the process was otherwise the same as in Example 1, to obtain polyether polymers 3-13. The above-mentioned tests were performed using the obtained polyether polymers 3-13, and the results are shown in Table 1.

[0247] [Comparative Example 4]

[0248] The polyether polymer 1 obtained in Example 1 was replaced with polyethylene oxide (weight-average molecular weight 20,000, manufactured by Fujifilm and Koichi Chemical Co., Ltd.). Otherwise, the polyether electrolyte solution 13 was prepared in the same manner as in Example 1, and the above-mentioned tests were performed. The evaluation results are shown in Table 1.

[0249] [Table 1]

[0250]

[0251] As shown in Table 1, the polyether polymers of the embodiments containing more than 20 mol% of the structural unit X unit derived from oxetane as shown in the aforementioned general formula (1) are able to suppress side reactions with sulfide-based solid electrolytes and have high ion mobility numbers.

[0252] Industrial availability

[0253] The polyether polymer of the present invention, the polyether electrolyte for lithium-ion secondary batteries using the polyether polymer, the composite solid electrolyte for lithium-ion secondary batteries, and the lithium-ion secondary batteries can suppress side reactions with sulfide-based solid electrolytes and have high ion mobility numbers. Therefore, they are useful in batteries for electric vehicles, hybrid vehicles, and other vehicles, batteries for household power storage, batteries for electronic devices such as mobile phones and personal computers.

Claims

1. A polyether polymer comprising at least 20 mol% X units per 100 mol% of structural units, said X units being structural units derived from oxetane as shown in the following general formula (1), In the formula, R 1 Whether the same or different, it is an alkyl group with 1 to 6 carbon atoms, R 2 Whether they are the same or different, it is -CH2O(CH2). a O(CH2) b The alkylene glycol alkyl ether group represented by H has the same or different repeating unit number a, which is an integer from 1 to 10, and the same or different repeating unit number b, which is an integer from 0 to 6.

2. The polyether polymer according to claim 1, further comprising Z units, said Z units being structural units derived from oxetane as shown in the following general formula (2), In 100 mol% of structural units, the content of X unit is 20~99.9 mol%, and the content of Z unit is 0.1~20 mol%. In the formula, R 1 Whether the same or different, it is an alkyl group with 1 to 6 carbon atoms, R 4 Same or different, for -CH2OR 8 The crosslinking group shown contains an olefinic unsaturated double bond, R 8 The same or different, being acryloyl, methacryloyl, allyl, or methylallyl.

3. A polyether electrolyte for lithium-ion secondary batteries, comprising the polyether polymer of claim 1 or 2 and a lithium salt compound.

4. A composite solid electrolyte for lithium-ion secondary batteries, comprising an inorganic solid electrolyte and the polyether electrolyte for lithium-ion secondary batteries as described in claim 3.

5. The composite solid electrolyte for lithium-ion secondary batteries according to claim 4, wherein, Inorganic solid electrolytes are sulfide-based solid electrolytes.

6. A lithium-ion secondary battery that uses the polyether electrolyte for lithium-ion secondary batteries as described in claim 3.

7. A lithium-ion secondary battery that uses the composite solid electrolyte for lithium-ion secondary batteries as described in claim 4.

Citation Information

Patent Citations

  • Laminate

    JP2020107414A